PERSONAL MEANING OF ACADEMIC EXPERIENCE: A COMPARISON OF INTRINSICALLY AND EXTRINSICALLY MOTIVATED GRADUATE STUDENTS - Pipere, Anita; Iliško, Dzintra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
To analyse the similarities and differences in personal meaning of academic experience associated with intrinsic and extrinsic academic motivation, the conceptual ideas of Self-Determination theory were blended with methodological elaborations based on the Dialogical Self Theory. The Academic Motivation Scale to identify intrinsically and extrinsically motivated graduate students and the Self Confrontation Method to disclose the important experiences in past, present and future related to the graduate studies were administered to 128 graduate students at the Daugavpils University. Both the quantitative and qualitative data analysis contributed to the understanding of relationships between the types of academic motivation and personal meaning of academic experience. The main differences in students’ personal meaning of academic experience, expressed in narrative themes were following: self-development, ideas about the further studies and factors inhibiting graduate studies were more frequent for intrinsically motivated students, while external support from influential persons, work/career, and past experience influencing current academic life were mentioned more often by extrinsically motivated students. The obtained results may help to develop more effective teaching strategies and institutional support of graduate students.